Evaluation of Pap Smear Results of Women in the Turkish Population by Age Group - Fatma Horasan; Esin Kasap (IMR Press, 2023)
Background: Cervical cancer is one of the leading malignancies affecting women globally, particularly in developing nations. The Pap smear is a crucial diagnostic tool for early detection and prevention of cervical cancer. This study aimed to evaluate the Pap smear results of patients who visited the clinic over a two-year period. Methods: A total of 620 patients who visited the clinic between January 2015 and December 2016 were included in this retrospective cohort study. Patients with a history of gynecological malignancy or hysterectomy were excluded. The Pap smear results were evaluated using the Bethesda 2001 system. Descriptive statistics and analysis of variance (ANOVA) were employed for data analysis. Results: The majority of the 620 participants were young and middle-aged. Among the microscopic findings, superficial squamous cells, polymorphonuclear (PMN) leukocytes, lactobacilli, squamous metaplasia, mature squamous cells, immature squamous cells, and endocervical cells were observed. The presence of transformation components, other quality indicators, and non-neoplastic conditions varied significantly across different age groups. The incidence of bacteria in Pap smear results was higher in young female patients in Turkey compared to the literature. Conclusions: Pap smear tests may yield false results, warranting consideration of age and cultural differences, particularly among women from diverse populations. Although human papillomavirus (HPV) vaccination is cost-effective in preventing cervical precancerous lesions, the Pap smear remains a preferred and financially viable method, especially in underdeveloped and developing countries. The findings of this study contribute to the existing literature, and emphasize the importance of expanding cervical cancer screening programs and raising awareness among women. Large-scale multicenter studies are warranted to further validate these findings.